SPATIAL AND STRUCTURAL ASPECTS OF AN ADAPTABLE BUILDING (DIMENSI: Journal of Architecture and Built Environment, 2017)
At the moment, in the era of energy crisis and climate change, designing a sustainable building is mandatory to minimize building construction and operational impacts, and to ensure the sustainability of the ecology. Prolong the life span of the building is one important strategy to achieve a sustainable building. Longer life span can be achieved if the building has continual adaptability towards changes of needs along its life span. This paper presents the design of an adaptable building with a modular, movable, and knock-down construction. In here, two important aspects in the creation of an adaptable building – the spatial and structural aspects, are considered. The result is a sustainable building with flexible and fluctuating space which is able to adapt to different functional requirements